Left sylvian subarachnoid neurocysticercosis: a therapeutic challenge - Vargas-Urbina, John (2023)
Introduction: Neurocysticercosis is a disease with high neurological morbidity, where subarachnoid subtype is a severe form. Secondary vasculitis is rare, but it can cause a stroke. The diagnosis is made by serology with enzyme-linked immunotransfer blot (ELIB) and tomography or resonance images with 3D sequence. Treatment is mainly medical. Case of report: A 28-year-old male with headache, expression aphasia and dysarthria. The images show a left frontal stroke, as well as a non-viable left temporal cyst and another viable left sylvian lesion, with positive ELIB. He was treated with clinical improvement. At 8 months, imaging control was performed due to new stroke. We saw reduction in size of the lesions, but still positive ELIB, so medical treatment was restarted with slow improvement of symptoms. Conclusion: Subarachnoid neurocysticercosis is a complex pathology, which requires multidisciplinary treatment, mainly medical, with difficult adherence to it due to its prolonged duration.